Exploration of Road Traffic Emissions and Their Impact on Air Quality in and around of Annaba City (North East Algeria) - Halimi, Samia; Mizane, Nour El Houda (International Journal of Environment, Agriculture and Biotechnology, 2023)
Global climate is warming, and the effects of climate change are associated with many causes; among them are the Greenhouse gas emissions from motor vehicles and factories. The study of exposure to air pollution related to road traffic in Annaba’s region is based on the results of air analyses, which shows that air temperatures are frail, accompanied by a very high humidity due mainly to the presence of the sea and many bodies of water (Fetzara Lake). This can allow the accumulation of certain pollutants such as carbon monoxide and dust (contents of CO and dust exceed the WHO standards), while some pollutants are present in small to negligible quantities such as NO, NO2, and SO. The air quality of Annaba and its surroundings (El Bouni, Sidi Ammar) can be generally described as good. Nevertheless, the existence of strong pollution due to the dust is noted close to the industrial complexes specially El Hadjar.